The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ctm2.231
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms of interactions between lung‐origin telocytes and mesenchymal stem cells to treat experimental acute lung injury

Abstract: 1. TCs can accelerate the migration of MSCs from the intraperitoneal space into injured lung tissues through intercellular signals and/or cell-cell interaction. 2. Pre-activated MSCs and TCs with LPS show more efficient in cell-cell communication by OPN-or EGFR-dominated signal pathways

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“… 27 OPN‐dominated molecular networks were also found to play an important role in lung tissue injury and repair and might be the decisive factor of therapeutic interaction between telocytes and stem cells. 28 During inflammation, OPN could increase leukocyte migration into inflammatory loci through multifactor regulations, for example, monocyte chemoattractant protein 1, β1 integrin, and PI3K. 29 The present study found that OPN gene overexpressed in three subtypes of NSCLC and was correlated with high metastasis and mortality rates of patients with NSCLC.…”
Section: Discussionmentioning
confidence: 52%
“… 27 OPN‐dominated molecular networks were also found to play an important role in lung tissue injury and repair and might be the decisive factor of therapeutic interaction between telocytes and stem cells. 28 During inflammation, OPN could increase leukocyte migration into inflammatory loci through multifactor regulations, for example, monocyte chemoattractant protein 1, β1 integrin, and PI3K. 29 The present study found that OPN gene overexpressed in three subtypes of NSCLC and was correlated with high metastasis and mortality rates of patients with NSCLC.…”
Section: Discussionmentioning
confidence: 52%
“… 1 , 2 During ALI, inflammatory response-activated neutrophils and macrophages can infiltrate into lung tissues and release cytokines, activating local pro-inflammatory reaction. 3 Innate immune signaling receptor NOD-like receptor family pyrin domain containing 3 (NLRP3) could be triggered by various danger signals including damage-related molecular patterns (DAMPs) and pathogen associated molecular patterns (PAMPs). 4 NLRP3 is the core assembly of inflammasome, the activation of which may give rise to caspase 1-mediated proteolytic activation of the interleukin-18 (IL-18) and IL-1β, and induce pyroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on TCs in the respiratory system, Zhang et al established a rat model of acute lung injury and observed the effect of cotransplantation of TCs with mesenchymal stem cells. The results demonstrated that TCs had a synergic effect on the experimental lung injury's attenuation [69]. TCs were also previously implicated in the pathogenesis of a broad spectrum of chronic inflammatory and fibrotic diseases, including Crohn's disease, liver fibrosis, and psoriasis.…”
Section: Cardiac Telocytes In Cardiovascular Regenerative Medicine-recent Developmentsmentioning
confidence: 82%